Pengembangan Metode Ekstraksi Sokletasi Terhadap Kadar Flavonoid Ekstrak Etanol Daun Matoa (Pomitea Pinnata) - Pramana Mahardika, Made Surya; Wartini, Ni Made; Eka Putera W, I Komang (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology); Vol 8 No 1 (2021): Scientific Journal of Food Technology (March), 2022)
Socletation is a method or process of separation of a component contained in a solid substance by filtering repeatedly using a specific solvent, so that all the desired components will be isolated. Factors that influence the extraction process with socletation among others are the addition amount of solvents and the extraction time. The purpose of this study was to find out the amount of solvents and the extraction time of matoa leaf extract (Pomitea pinnata) using the Socletation method. Determination of the amount of solvents and the best extraction time in the extraction of matoa leaf extract using socletation method with a ratio amount of 96% ethanol solvent and material as much as 1:5 ; 1:10 ; 1:15 and variations in extraction time of 3 hours, 6 hours, 9 hours, and 12 hours. Determination of the amount of solvents and extraction time is best done by calculating the flavonoid levels of validated chronism-spectrophotometer methods. The method used was a laboratory experiment with descriptive analysis. The parameters tested included moisture content, total yield, and flavonoid levels. The results showed that all parameters tested had met the requirements with return value % (80-110%); linearity with a value of r = 0.9954 (r > 0.95); LOD value 2,397ppm; LOQ value 7,988 ppm; precision <2%. Water content of fresh leaves were 69.18% and dry leaves were 10.36%; yield rate value increased in each treatment. The best amount of solvents was at a ratio of 1:10 with an extraction time of 3 hours.